When traditions meet different approaches: the case of exophoric Lithuanian demonstrative pronouns - Judžentytė-Šinkūnienė, Gintarė (Lietuvių kalba, 2020)
This paper aims to review the existing research on the exophoric Lithuanian demonstrative pronouns and to give a short review of other possible parameters alongside the distance that influences the choice of demonstratives as well as the applied methods in the field. It also suggests some key aspects for the analysis of the exophoric use of demonstrative pronouns.
Keywords: demonstrative pronouns; exophoric usage; Lithuanian; review